TAHAP PERKEMBANGAN KOGNITIF PESERTA PROGRAM PENDIDIKAN MORAL DAN ETIKA TENTARA DALAM ANGKATAN TENTARA MALAYSIA - Mokhtar, Azri; Wan Mamat, Wan Hasmah; Darussalam, Ghazali; Supriyatno, Triyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
This article discusses about cognitive development among military personnel in the Moral and Military Ethical Education programs (MMEE) in the Malaysian Armed Forces (MAF). This study was conducted to evaluate the influence of the elements used in the MMEE’s program to cognitive performance among the participants. A total of 469participants took a moral and military ethical (MME) achievement test and the data were analyzed using multiple regression analysis. The findings show that, out of the five key elements of MMEE’s program, elements of the table shows that there is a significant contribution to cognitive achievement by the contribution of = 1.4 % . The remaining elements of the syllabus, facilities, location and teaching and learning process of each show there is no significant contribution to cognitive achievement among theparticipants.